2015
DOI: 10.1080/15389588.2014.949340
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Attitudes About Distracted Driving in College Students

Abstract: Distracted driving is a highly prevalent behavior among college students who have higher confidence in their own driving skills and ability to multitask than they have in other drivers' abilities. Drivers' self-efficacy for driving and multitasking in the car, coupled with a greater likelihood of having witnessed DD behaviors in others, greatly increased the probability that a student would engage in DD. Most students felt that policies, such as laws impacting driving privilege and insurance rate increases, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 25 publications
(23 reference statements)
7
33
1
1
Order By: Relevance
“…This finding is consistent with the literature, as most studies report high optimism bias and low perceived susceptibility among this age group (Hill, et al, 2015). While hands-free and Bluetooth devices were seen as safer, these are still significantly risky activities compared to not using a phone at all when driving (Liu & Ou, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is consistent with the literature, as most studies report high optimism bias and low perceived susceptibility among this age group (Hill, et al, 2015). While hands-free and Bluetooth devices were seen as safer, these are still significantly risky activities compared to not using a phone at all when driving (Liu & Ou, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Distracted driving was common, with texting and driving being most typical, as is supported by the literature (Cook & Jones, 2011;Hill et al, 2015). Research is needed to overcome the perceived barriers and lack of perceived threat of texting and driving, as found both here and in other studies (Hill, et al, 2015).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Young drivers who perceived themselves as good drivers were more likely to monitor/read and respond to communications on their smartphone. Previous research has shown that it is not uncommon for young drivers to perceive themselves as having a greater skill level than their peers and confidence in their ability to multitask (e.g., Hill et al, 2014). This overinflated belief in driving ability can lead to greater engagement in dangerous driving behaviours such as mobile phone use (Hill et al, 2014).…”
Section: Critical Belief Possible Message Content and Strategiesmentioning
confidence: 99%
“…Previous research has shown that it is not uncommon for young drivers to perceive themselves as having a greater skill level than their peers and confidence in their ability to multitask (e.g., Hill et al, 2014). This overinflated belief in driving ability can lead to greater engagement in dangerous driving behaviours such as mobile phone use (Hill et al, 2014). A recent simulator study of undergraduate students in an American university (Mage = 21.8 years) found that there was no correlation between self-assessment of driving safeness and actual driving errors (Sanbonmatsu, Strayer, Biondi, Behrends, & Moore, 2015).…”
Section: Critical Belief Possible Message Content and Strategiesmentioning
confidence: 99%